Sobre el tabú, el tabú lingüístico y su estado de la cuestión. - Calvo Shadid, Annette (2012)
This article deals with a study of the term "taboo", its origins and approaches, and it focuses on the linguistic taboo, its conception and preliminary studies taking the classification proposed by Martínez Valdueza (1998) in two periods: studies before 1970 and studies after that year. It concludes showing how, throughout history, this topic has been developed in its way of treatment and scopes.